Strategi Peningkatan Kompetensi Siswa melalui Implementasi Kurikulum Merdeka di MA Zainul Anwar - Romlah, Siti; Quthny, Abu Yazid Adnan; Ma’arif, Mohamad Ahyar (Attractive : Innovative Education Journal, 2024)
This research is to find out a strategy to increase competency at the MA Zainul Anwar institution. How to implement the Independent Curriculum, which is an important tool in the learning process and is always updated in accordance with societal developments, where the main objectives are students, society and subjects. Speed plays an important role for an educational institution in creating learning tools that involve planning and learning. Based on this background, the formulation of this research problem is how to improve student competency strategies by implementing an independent curriculum at MA Zainul Anwar. This research uses qualitative research methods obtained through interviews, observation, documentation and taking studies from several educational journals. Use This qualitative method makes it easier to obtain relevant information or data. Based on the research results, it can be concluded that through the independence policy, MA Zainul Anwar has started efforts to increase the competence of his students through learning the Merdeka Curriculum, Eskrakuriler and talent interests to improve Human Resources. Keywords: Student Competencies, Merdeka Curriculum, Increasing Student Competencies,